PENGARUH CEO POWER, LIKUIDITAS, KEPEMILIKAN INSTITUSIONAL, DAN UKURAN PERUSAHAAN TERHADAP PERINGKAT SUKUK - Darul Wiyono (Cakrawala Management Business Journal, 2021)
This study aims to examine the CEO power, liquidity, institutional ownership, and size of sukuk ratings on companies that issue sukuk and listed on the Indonesia Stock Exchange for the period 2013-2017. The independent variables in this study are CEO power, liquidity, institutional ownership, and size, while the dependent variable in this study is sukuk rating. The data used in this study are secondary data obtained from the official website of Indonesia Stock Exchange. The population of this study was 26 companies and total of sample is 10 companies selected using purposive sampling method. This study uses the ordinal logistic regression method to determine the variable that have an impact on sukuk rating. The result are variable CEO power and size have a effect on sukuk ratings, meanwhile variable liquidity and institutional ownership have not a effect on sukuk ratings.